Analisis Pemanfaatan Layanan BPJS Kesehatan Di UPT Puskesmas Medan Sunggal Tahun 2025 - Sitepu, Dhea Salsabila Br.; Lubis, Irwansyah; Wardani, Icha Febi; Aulia, Supangge Tiara; Darus, Nanda Fadilah; Novrinda, Nazla; Salsabila, Mutiara; Cahaya, Fika Ayu (Yayasan Jompa Research and Development, 2025)
One of the programs organized by the Indonesian Government is the implementation of the National Health Insurance (JKN) program organized by the Social Security Administering Agency (BPJS). Health centers in the JKN/BPJS system have a major role for BPJS health participants. If the health center services provided are good, more BPJS participants will utilize health services. This study aims to determine how patient knowledge and perceptions are with the utilization of BPJS Health services at the Medan Sunggal Health Center. The type of study used a qualitative approach method with in-depth interviews with one of the Medan Sunggal health center staff. The data collection technique used was a semi-structured in-depth interview and documentation to one of the special staff at the Medan Sunggal Health Center UPT. The results of this study indicate that the Medan Sunggal Health Center has provided the best and most comfortable service in implementing BPJS, this can be seen from the large number of patient visits each month.